PERKEMBANGAN PSIKOSOSIAL ANAK DAN REMAJA PASCA ERUPSI SINABUNG DI KABUPATEN KARO - Wardiyah Daulay; Mahnum Lailan Nasution; Sri Eka Wahyuni (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The eruption of Mount Sinabung is a natural disaster that occurred in Batukarang Village, Payung District, Karo Regency. In addition to physical conditions, this disaster affected the psychosocial condition of the community, especially children and adolescents. As a result of disasters, children and adolescents experience anxiety, stress, fear, PTSD, depression, etc. These symptoms can affect the development of adolescents themselves. This study aims to determine the psychosocial development of children and adolescents after the Sinabung eruption. Descriptive research design with a sample of 94 school-age children and 94 adolescents. The sampling technique is purposive sampling. The results showed that the psychosocial development of school-age children was in good category as many as 6 children (6.4%), and sufficient psychosocial development was 88 children (93.6%). While the psychosocial development of adolescents 81.9% experienced sufficient psychosocial development, 18.1% adolescents experienced good psychosocial development. The results of this study can assist mental nurses in providing psychological and social support after a disaster with a mental nursing approach so that the psychosocial development of disaster victims, especially adolescents, goes well and can improve the mental health of disaster victims.